Decision-Making Deficits Are Associated With Learning Impairments in Female College Students at High Risk for Anorexia Nervosa: Iowa Gambling Task and Prospect Valence Learning Model - Na, Eunchan; Kang, Bitna; Kim, Myung-Sun (Frontiers in Psychiatry, 2019)
This study investigated deficits in decision-making ability in female college students with anorexia nervosa (AN) symptoms using the Iowa Gambling Task (IGT) and the prospect valence learning (PVL) model. Based on scores on the Korean version of the Eating Attitude Test-26 (KEAT-26), subjects were assigned to either the nonclinical AN (nAN) group (n = 42) or the control group (n = 43). The nAN group exhibited significantly lower total net scores and block net scores on the third, fourth, and fifth blocks of the IGT than did the control group. The nAN group selected cards significantly more often from the disadvantageous A and B decks and less often from the advantageous D deck than did the control group. In addition, the block net scores of the nAN group did not differ across the five blocks, whereas those of the control group increased as the trials progressed. There was a significant negative correlation between IGT total net score and total score on the KEAT-26. The nAN group had significantly lower values than the control group on the learning and response consistency parameters of the PVL model. These results indicate that female college students with AN symptoms have deficits in decision-making ability, and that these deficits are related to difficulties in remembering experience obtained from earlier trials and applying it to later trials. These difficulties further lead them to make decisions randomly. A deficit in decision-making ability could serve as a trait marker for AN.